2022
DOI: 10.1002/mp.15655
|View full text |Cite
|
Sign up to set email alerts
|

Automated estimation of total lung volume using chest radiographs and deep learning

Abstract: Background Total lung volume is an important quantitative biomarker and is used for the assessment of restrictive lung diseases. Purpose In this study, we investigate the performance of several deep‐learning approaches for automated measurement of total lung volume from chest radiographs. Methods About 7621 posteroanterior and lateral view chest radiographs (CXR) were collected from patients with chest CT available. Similarly, 928 CXR studies were chosen from patients with pulmonary function test (PFT) results… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Earlier work has shown promising results for producing PFT results at a patient level using convolutional neural networks. For example, total lung volume has been estimated from chest radiographs 16 and CT scans have been used for estimating spirometry test results 17 . These methods did not produce lobe level estimates.…”
Section: Related Workmentioning
confidence: 99%
“…Earlier work has shown promising results for producing PFT results at a patient level using convolutional neural networks. For example, total lung volume has been estimated from chest radiographs 16 and CT scans have been used for estimating spirometry test results 17 . These methods did not produce lobe level estimates.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, some deep learning techniques are used for calculating lung volume capacity. Ecem Sogancioglu et al [22] proposed an automated method for estimating total lung volume using CXR and deep learning. They used posteroanterior and lateral view CXR with five different deep learning architectures: DenseNet121, ResNet34, ResNet50, VGG-Net19, and six layers CNN.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Machine learning has resulted in breakthroughs in medical image analysis in recent years, and several studies have used general image recognition models in medical image analysis and the estimation of functional parameters and other information from images ( 19 ). Sogancioglu et al ( 20 ) reported the use of artificial intelligence (AI) for the estimation of the lung volume from pseudo-CXRs calculated from CT images. However, the estimated lung volumes were calculated from CT image data and not pulmonary function values.…”
Section: Introductionmentioning
confidence: 99%